2020
DOI: 10.48550/arxiv.2009.07852
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unraveling the Dirac Neutrino with Cosmological and Terrestrial Detectors

Peter Adshead,
Yanou Cui,
Andrew J. Long
et al.

Abstract: We propose a method for testing the Dirac neutrino hypothesis by combining data from terrestrial neutrino experiments, such as tritium beta decay, with data from cosmological observations, such as the cosmic microwave background and large scale structure surveys. If the neutrinos are Dirac particles, and if the active neutrinos' sterile partners were once thermalized in the early universe, then this new cosmological relic would simultaneously contribute to the effective number of relativistic species, N eff , … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…When T drops below m H 0 ,A m H + , on the other hand, the effective fourneutrino interaction Γ ν L ν s,R mediated by the neutral scalars can still be strong enough to maintain the thermalization of ν s,R . As a consequence, ν s,R can play the role of extra radiation in affecting the Hubble expansion both at the early BBN and at the late CMB epoch, which can be parameterized by a shift of the effective neutrino number [26][27][28][29][30]:…”
Section: Mimicking the H0 Solution Via An Effective Neutrino Number S...mentioning
confidence: 99%
See 1 more Smart Citation
“…When T drops below m H 0 ,A m H + , on the other hand, the effective fourneutrino interaction Γ ν L ν s,R mediated by the neutral scalars can still be strong enough to maintain the thermalization of ν s,R . As a consequence, ν s,R can play the role of extra radiation in affecting the Hubble expansion both at the early BBN and at the late CMB epoch, which can be parameterized by a shift of the effective neutrino number [26][27][28][29][30]:…”
Section: Mimicking the H0 Solution Via An Effective Neutrino Number S...mentioning
confidence: 99%
“…Despite the intensive focus on Majorana neutrinos during the past decades, the topics with neutrinos treated as being of Dirac nature are attracting much attention, especially in connection with the big-bang nucleosynthesis (BBN) and cosmic microwave background (CMB) [26][27][28][29][30], as well as the baryon asymmetry of the Universe [31,32]. The Dirac neutrino effects in the b → sµ + µ − process have been noticed in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Upcoming CMB Stage IV (CMB-S4) experiments are expected to put much more stringent bounds than Planck due to their potential of probing all the way down to ∆N eff = N eff − N SM eff = 0.06 [93]. For some recent studies on light Dirac neutrinos and enhanced ∆N eff in different contexts, please see [56,[94][95][96][97][98][99][100].…”
Section: Relativistic Degrees Of Freedom N Effmentioning
confidence: 99%
“…Recently, we have demonstrated that a purely thermal Dirac leptogenesis (PTDL) mechanism [3,4] can establish a more direct link between the low-energy leptonic CP violation and the highscale lepton asymmetry, where the BAU is formulated by the neutrino mixing without invoking specific Yukawa textures. In addition to the intimate relation with the BAU mystery, the right-handed Dirac neutrinos can also have a significant impact on the evolution of the early Universe, e.g., via generating the effective neutrino number shift, ∆N ef f , which is constrained by the big-band nucleosynthesis (BBN) [5][6][7][8] and cosmic microwave background (CMB) observations [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%